THE INFLUENCE OF DIFFERENTIATED LEARNING WITH THE APPLICATION OF PROBLEM BASED LEARNING MODELS ON MATHEMATICS LEARNING OUTCOMES - Cantika Meiysalika Harahap; Nurlina Ariani Hrp; Laili Habibah Pasaribu (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
The learning model used is Problem Based Learning Education is an investment in the future of a nation. Therefore, special attention is needed to educators and the quality of education provided.The purpose of this study is to see the learning outcomes of students using the Problem Based Learning learning model,To find out whether there is an influence of differentiated learning with the application of the Problem Based Learning Model on the Mathematics Learning Outcomes of Junior High School Students at Panglima Polem Rantauprapat.This research method uses data in the form of numbers as a measuring tool because the research used uses a quantitative approach. The validity or otherwise of a study depends on the type of data collection used to select the right method according to the type of research.The results of this study arefound that the teaching and learning process using Problem Based Learning can improve students' understanding of mathematical concepts. In this study, students who participated in project-based learning had a deeper understanding of mathematical concepts compared to students who participated in traditional learning and could significantly improve student learning outcomes.This approach creates a more interactive and immersive learning environment, which has a positive impact on their academic achievement.